2018
DOI: 10.1038/s41598-018-22045-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pulsed runoff-erosion events under typical rainstorms in a small watershed on the Loess Plateau of China

Abstract: The pulsed events of rainstorm erosion on the Loess Plateau are well-known, but little information is available concerning the characteristics of superficial soil erosion processes caused by heavy rainstorms at the watershed scale. This study statistically evaluated characteristics of pulsed runoff-erosion events based on 17 observed rainstorms from 1997–2010 in a small loess watershed on the Loess Plateau of China. Results show that: 1) Rainfall is the fundamental driving force of soil erosion on hillslopes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 47 publications
0
17
0
1
Order By: Relevance
“…The highest sediment concentration maybe reaches as high as about 1000 kg/m 3 in erosion-prone soil areas under special rainfall conditions [28,29] , but the investigated value in the existed researches is much lower than this possible maximum. Therefore, it is of great importance to evaluate the measurement error of traditional stirring-sampling method for the full range of possible sediment concentrations for various soil types and its correction possibility, so as to provide a reliable basic data for soil erosion research.…”
Section: Introduction 1mentioning
confidence: 90%
“…The highest sediment concentration maybe reaches as high as about 1000 kg/m 3 in erosion-prone soil areas under special rainfall conditions [28,29] , but the investigated value in the existed researches is much lower than this possible maximum. Therefore, it is of great importance to evaluate the measurement error of traditional stirring-sampling method for the full range of possible sediment concentrations for various soil types and its correction possibility, so as to provide a reliable basic data for soil erosion research.…”
Section: Introduction 1mentioning
confidence: 90%
“…For example, to address the relationship between land use and response of soil erosion, Wang Huan et al (2019) carried out quantitative attribution on soil erosion in different geomorphic areas of Sanchahe watershed, which showed that land use had the highest explanatory power for soil erosion, and the soil erosion risk of cultivated land was higher than that of other land use types (Borrelli et al 2017b;Dai et al 2017;Li et al, 2018). Based on the fixed-point monitoring of slope surface, the influence of different rainfall intensity on soil erosion mode is significant (Fullhart et al 2020;Wu et al 2018), and the spatial distribution of soil erosion directly affects the spatial change of soil nutrient loss (Zeng et al 2018). In addition, relevant researches have been carried out on the mechanism of soil erosion (Li et al 2017;Peng and Wang 2012;Shen et al 2008;Wang et al 2013a) , the construction of soil erosion model (Geissen et al 2008;Kheir et al 2010;Liu 2016;Xu et al 2008) and the temporal and spatial variation of soil erosion (He et al 2018;Wang et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion causes land degradation, which can lead to problems in water and food security worldwide (Auerswald & Kutilek, 1998; de Vente, Poesen, & Verstraeten, 2013; Fang, Wang, & Shi, 2017; Komissarova & Paramonova, 2019). In China, soil erosion has become a serious environmental issue that limits the sustainable development of the economy (Abbas, Warrington, & Lei, 2019; Guo, Ma, Cai, et al, 2018; Wu, Jiang, Li, & Ma, 2018).…”
Section: Introductionmentioning
confidence: 99%